ANALISIS PENGARUH DISIPLIN KERJA, KEPUASAN KERJA, DAN GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN (Studi pada Karyawan Bagian Produksi PT. Nyonya Meneer Semarang) - Qodarini, Fika Laela; Nugraheni, Rini (Diponegoro Journal of Management, 2015)
This study aims to examine and analyze the effect of Â work discipline, job satisfaction, and leadership style on the performance of the production employees of PT. Nyonya Meneer Semarang. This study uses three independent variables, namely work discipline, job satisfaction, and leadership style with one dependent variable is the performance of employees.This study data collection method using interviews and questionnaires. Sampling techniques in this study using simple random sampling method. The data analysis methods used in this study include the validity of the test, reliability test, the classical assumption test, multiple linear regression analysis, coefficient determination, and the F test and t test.Based on the analysis, the results showed that work discipline, job satisfaction, and leadership style influences positive and significant on employees performance. The coefficient of determination shows that the performance of the production employees of PT. Nyonya Meneer Semarang is 50,5% affected by work discipline, job satisfaction, and leadership style. The other variables that this study does not use influence the rest of it, which is 49,5%.